Kinetic study of crystallization of PHB in presence of hydroxy acids - Souza, Josiane de Lima [UNESP]; Kobelnik, Marcelo [UNESP]; Ribeiro, Clovis Augusto [UNESP]; Vieira Capela, Jorge Manoel [UNESP]; Crespi, Marisa Spirandeli [UNESP] (Springer, 2009)
Poly(3-hydroxybutyrate), PHB, has been structurally modified through reaction with hydroxy acids (HA) such as tartaric acid (TA) and malic acid (MA). The crystallization kinetic of the samples was evaluated by isoconversional method through nonlinear fitting to obtain the estimation for activation energy (E (a) ) and pre-exponential (A) values. The thermal behavior of the crystallization temperature, 44.8 and 58.9 A degrees C at 5 A degrees C/min, and results obtained to the average activation energy, 73 +/- A 9 kJ mol(-1) and 63 +/- A 1 kJ mol(-1), to PHB/MA and PHB, respectively, are suggesting that malic acid may be deriving plasticizer units from its own PHB chain. PHB/TA show increase in the medium value of E (a), 119 +/- A 2 kJ mol(-1) and T (c) = 48.2 A degrees C (at 5 A degrees C/min), indicating that tartaric acid is probably interacts in different way to the of PHB chain (E (a)=73 +/- A 9 kJ mol(-1), T (c) = 44.8 A degrees C at 5 A degrees C/min).
Keywords: PHB; PHB-hydroxyacids; Nonlinear fitting; Crystallization; Nonisothermal kinetic